Training for speed, power and strength (Peak Performance, 2006)
Anyone who has ever considered Peak Performance biased towards endurance sports and events can bask happily in the almost entirely explosive emphasis of this special report. It will not help you to work out/run/swim/cycle for longer (although there are other reports in the series that do just that) but it will give you the knowledge and the tools you need to enhance your speed, increase your power and boost your strength. Prepared for you by PP`s expert conditioning duo, John Shepherd and Raphael Brandon, the report covers a wide range of interests, from strength training for swimmers (gym exercises designed to replicate water action as closely as possible) to rotational power training (very useful for mall sports involving sudden turns); from speed development (drills to help you run like the wind) to battling the ageing process (sadly speed declines much faster than endurance with the passing years); and from weight possible for any athlete to ignore these days) to agility training (much more than optimum sports technique). In all these articles you will find not just a distillation and critique of the latest scientific research but a variety of carefully selected, highly-targeted practical drills, techniques and exercises which will help you to enhance your own abilities, whatever your chosen sport or activity. You will not just want to read it once but keep it by your side to refer to again and again, and use it to track your inevitable progress